2021
DOI: 10.3390/ijerph18137014
|View full text |Cite
|
Sign up to set email alerts
|

Review of the Health, Welfare and Care Workforce in Tasmania, Australia: 2011–2016

Abstract: Background: On a per capita basis, rural communities are underserviced by health professionals when compared to metropolitan areas of Australia. However, most studies evaluating health workforce focus on discrete professional groups rather than the collective contribution of the range of health, care and welfare workers within communities. The objective of this study was therefore to illustrate a novel approach for evaluating the broader composition of the health, welfare and care (HWC) workforce in Tasmania, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Adopting a rural pipeline approach, 25 course offerings at these campus locations should reflect consideration of local workforce shortages. The north west coast of Tasmania has historically experienced the lowest per capita numbers of nursing, medicine and allied health professionals 16 . However, this study found that courses such as medicine, paramedicine, pharmacy and psychology, all of which recorded higher numbers of regional students than rural have, historically, only been available at the Hobart campus.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Adopting a rural pipeline approach, 25 course offerings at these campus locations should reflect consideration of local workforce shortages. The north west coast of Tasmania has historically experienced the lowest per capita numbers of nursing, medicine and allied health professionals 16 . However, this study found that courses such as medicine, paramedicine, pharmacy and psychology, all of which recorded higher numbers of regional students than rural have, historically, only been available at the Hobart campus.…”
Section: Discussionmentioning
confidence: 62%
“…The north west coast of Tasmania has historically experienced the lowest per capita numbers of nursing, medicine and allied health professionals. 16 However, this study found that courses such as medicine, paramedicine, pharmacy and psychology, all of which recorded higher numbers of regional students than rural have, historically, only been available at the Hobart campus. Offering courses for health professions which are in short supply at the Launceston and Cradle Coast campuses, attracting local students and providing quality rural training experiences will all likely positively contribute to rural health workforce growth and distribution across the state.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The GPs interviewed believed lack of access to services of all types and the limited range of services in the community were major causes of PPHs. Understanding the views of the broader rural health workforce, its service gaps, and potential capacity may be useful for future workforce planning and resources allocation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%